Pengaruh Media Interaktif Baamboozle terhadap Minat Belajar Siswa dalam Pembelajaran IPS - Nabila, Fadhilatun; Aisyah Nur Sayidatun Nisa (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2026)
This study aims to determine the effect of the use of interactive media bamboozle on students' learning interest in learning social studies on the material of the Role of Society in the Economic Chain. This study uses a quantitative research design to measure the effect of interactive media Bamboozle on students' learning interest in learning social studies. Data from the experimental and control classes were collected using pretests and posttests as well as observation sheets to measure students' learning interest with a 4-point Likert scale. The results of this study indicate that the use of interactive media bamboozle has a positive effect on students' learning interest in learning social studies on the material of the role of society in the economic chain. The conclusion of this study is that interactive learning media Baamboozle has a positive effect in increasing students' learning interest as indicated by students' responses during learning. The use of interactive media Baamboozle is able to arouse students' learning interest so that students are more enthusiastic in learning social studies. ​Keywords: Baamboozle Media, Influence, Learning Interest, Social Studies Learning